Lithium ion battery positive pole piece, lithium ion battery and electric device

By using quaternary system active materials and transition metal-doped lithium iron manganese phosphate materials in the positive electrode of lithium-ion batteries, and designing conical holes on the surface of the electrode, the capacity attenuation problem of lithium-ion batteries under high temperature and long cycles is solved, and a balance between high energy density and safety is achieved.

CN120767288APending Publication Date: 2025-10-10JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510931400.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-07
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

Existing lithium-ion batteries suffer severe capacity degradation under high-temperature and long-cycle conditions due to the structural instability and poor thermal stability of high-nickel materials, making it difficult to achieve both high energy density and safety.

Method used

The quaternary system active material LiNixCoyMnzAl1-xy-zO2 and transition metal-doped lithium iron manganese phosphate LiMnaFebMcPO4 are used as the positive electrode material, and conical holes are designed on the surface of the electrode, combined with carbon nanotube and graphene composite conductive agents to improve electronic conductivity and electrolyte wettability.

Benefits of technology

It improves the energy density and thermal stability of lithium-ion batteries, improves kinetic performance, slows down the capacity decay of high-nickel materials, and enhances the long-cycle charge and discharge performance and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120767288A_ABST
    Figure CN120767288A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a lithium ion battery positive pole piece, a lithium ion battery and a power utilization device, the lithium ion battery positive pole piece comprises a current collector, and a first positive coating and a second positive coating which are respectively arranged on two sides of the current collector; a plurality of conical hole grooves are formed in the surfaces of the first positive electrode coating and the second positive electrode coating in a punching manner; the first positive electrode coating and the second positive electrode coating respectively comprise a quaternary system active matter and transition metal doped lithium iron manganese phosphate, and the mass ratio of the quaternary system active matter to the transition metal doped lithium iron manganese phosphate is 7: 3-9: 1; the chemical general formula of the quaternary system active matter is LiNixCoyMnzAl1-x-y-zO2, wherein x is greater than or equal to 0.87 and less than or equal to 0.94, y is greater than or equal to 0.03 and less than or equal to 0.06, z is greater than or equal to 0.01 and less than or equal to 0.05, and x + y is less than or equal to 0.99; the chemical formula of the transition metal doped lithium ferric manganese phosphate is LiMnaFebMcPO4, a is more than or equal to 0.4 and less than or equal to 0.6, b is more than or equal to 0.4 and less than or equal to 0.6, c is equal to 1-a-b, and M comprises one or a combination of more of Mg, Ti, Zr, Nb, Ni, Co, F, B and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of lithium ion batteries, and particularly relates to a lithium ion battery positive electrode sheet, a lithium ion battery and an electric device. BACKGROUND

[0002] With the market demand for higher energy density and safety of batteries, a single material is difficult to balance. Although the commonly used high-nickel material can provide high energy density, its structural instability may cause structural collapse in the charge and discharge cycle. In addition, the poor thermal stability of high-nickel material has always been a bottleneck in its application, which will cause the battery capacity to decay intensively under high-temperature long cycle.

[0003] Therefore, how to overcome the battery capacity decay defect of the lithium ion battery containing high-nickel material under high-temperature long cycle environment is a technical problem to be solved in the field.

[0004] It should be noted that the above information disclosed in the background section is only used to understand the background of the present application, and therefore, the above description is not considered to constitute prior art information. SUMMARY

[0005] The present application at least provides a lithium ion battery positive electrode sheet, a lithium ion battery and an electric device.

[0006] In a first aspect, the present application provides a lithium ion battery positive electrode sheet, comprising: a current collector and first and second positive electrode coatings respectively arranged on both sides of the current collector; the surfaces of the first and second positive electrode coatings are provided with a plurality of conical holes; and the first and second positive electrode coatings respectively comprise quaternary system active material and transition metal doped lithium iron manganese phosphate, and the mass ratio of the quaternary system active material and the transition metal doped lithium iron manganese phosphate is 7:3-9:1; the chemical general formula of the quaternary system active material is LiNi x Co y Mn z Al 1-x-y-z O2, wherein 0.87≤x≤0.94, 0.03≤y≤0.06, 0.01≤z≤0.05 and x+y≤0.99; and the chemical formula of the transition metal doped lithium iron manganese phosphate is LiMn a Fe b M c PO4, wherein 0.4≤a≤0.6, 0.4≤b≤0.6 and c=1-a-b, and M includes one or a combination of several of Mg, Ti, Zr, Nb, Ni, Co, F, B, etc.

[0007] In an alternative embodiment, the quaternary system active material comprises quaternary system active material large particles and quaternary system active material small particles; wherein the D50 particle size of the quaternary system active material large particles is 9-13 μm, and the particle size distribution satisfies 0.2≤(D90-D10) / D50≤0.6; the D50 of the quaternary system active material small particles is 2.5-5 μm, and the particle size distribution satisfies 1.1≤(D90-D10) / D50≤1.6.

[0008] In an alternative embodiment, the positive electrode coating further comprises a conductive agent; the conductive agent is a carbon nanotube and graphene composite, and the mass ratio of the conductive agent to the total mass of the positive electrode coating is 2-5%.

[0009] In an alternative embodiment, the lithium iron manganese phosphate is in a core-shell structure, the inner core is FePO4, and the volume ratio is 85%-92%, and the shell is LiMnPO4, and the volume ratio is 8%-15%; wherein the shell thickness is 50-100 nm. a

[0010] In an alternative embodiment, the tap density of the lithium iron manganese phosphate is ≥2.3 g / cm3, and the specific surface area is 5-10 m2 / g. 3 2

[0011] In an alternative embodiment, the positive electrode coating further comprises a doped coated composite compound, and the dopant comprises any one or a combination of several of Al, Co, Ta, Ti, Nb, Zr, B, W, Mg, Te, Ca, Fe, Mo, Na, K, La, Ga, F, Cl, S, B and N.

[0012] In an alternative embodiment, the current collector is an aluminum foil coated with a carbon layer, the thickness of the carbon layer is 0.5-2 μm, the porosity is 15-25%, and the peeling strength between the positive electrode coating and the current collector is ≥10 N / m.

[0013] In an alternative embodiment, the width of the positive electrode tab is L1, and satisfies 50 mm≤L1≤120 mm, the distance between the conical hole groove and the two sides of the positive electrode tab width direction is D1 and D2 respectively; the thickness of the first positive electrode coating is h1, and satisfies 40 μm≤h1≤200 μm, and the depth of the conical hole groove is h3; the thickness of the second positive electrode coating is h2, and satisfies 40 μm≤h2≤200 μm, and the depth of the conical hole groove is h4; and the positive electrode tab simultaneously satisfies: 0.2L1≤D1≤0.23L1; 0.2L1≤D2≤0.23L1; 0.78≤h3 / h1≤0.85; 0.78≤h4 / h2≤0.85.

[0014] ​​​In a second aspect, the present disclosure also provides a lithium ion battery including the lithium ion battery positive electrode sheet as described above.

[0015] In a third aspect, the present disclosure also provides an electric device including the lithium ion battery as described above.

[0016] The lithium ion battery positive electrode sheet, the lithium ion battery, and the electric device provided by the present disclosure can improve the overall energy density of the battery by using high-nickel material active substances, can improve the kinetic performance of lithium iron manganese phosphate material by using high electronic conductivity, can reduce the dependence on cobalt and provide the thermal stability of high-nickel material by using the olivine structure of lithium iron manganese phosphate material, can slow down the capacity attenuation of high-nickel material in long cycles, and can improve the wettability of the electrolyte to the electrode sheet by the punching design of the positive electrode sheet, thereby improving the deintercalation capacity of lithium ions, improving the kinetic performance, and improving the charge-discharge performance and stability of the battery in long thermal cycles.

[0017] Other features and advantages of the present disclosure will be described in the following description, and some will become apparent from the description, or will be learned through practice of the present disclosure. The purposes and other advantages of the present disclosure will be realized and achieved by the structures specifically pointed out in the description and the accompanying drawings.

[0018] In order to make the above-mentioned purposes, features and advantages of the present disclosure more obvious and easy to understand, the following preferred embodiments are specifically described in detail below, and the accompanying drawings are described as follows. BRIEF DESCRIPTION OF DRAWINGS

[0019] In order to more clearly illustrate the specific embodiments of the present disclosure or the technical solutions in the prior art, the following will briefly introduce the drawings needed to be used in the specific embodiments or the prior art description. Obviously, the drawings in the following description are some embodiments of the present disclosure, and those skilled in the art can also obtain other drawings according to these drawings without creative labor.

[0020] Figure 1 A structural schematic diagram of a lithium ion battery roll core provided by the present disclosure is shown in the figure, wherein (a) is a winding schematic diagram, and (b) is a cross-sectional schematic diagram;

[0021] Figure 2 A top view of a positive electrode sheet provided by the present disclosure is shown in the figure;

[0022] Figure 3 A thickness direction cross-sectional view of a positive electrode sheet provided by the present disclosure is shown in the figure.

[0023] In the figure:

[0024] 1, separator; 2, negative electrode sheet; 3, positive electrode sheet;

[0025] 4, first positive electrode coating layer; 5, current collector; 6, second positive electrode coating layer;

[0026] 7, first punching area; 8, first positive electrode coating layer hole groove; 9, second punching area; 10, second positive electrode coating layer hole groove. DETAILED DESCRIPTION

[0027] In order to make the objects, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions of the present application will be described clearly and completely below with reference to the drawings. Obviously, the described embodiments are some embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present application.

[0028] As used herein, the phrases "in an embodiment", "according to an embodiment", "in some embodiments", and the like generally mean the fact that a particular feature, structure, or characteristic that follows the phrase can be included in at least one embodiment of the present disclosure. Therefore, the particular feature, structure, or characteristic can be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example", "exemplary", and the like are used as an example, instance, or illustration. Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. Instead, the use of the terms "example", "exemplary", and the like is intended to present the concept in a specific manner.

[0029] In this document, example embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as "at least one of" when following a list of elements modifies the entire list of elements and not the individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood as including only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.

[0030] The terminology used herein is for the purpose of describing particular example configurations only and is not intended to be limiting. As used herein, the singular articles "a", "an", and "the" can be intended to include the plural forms as well, unless the context clearly indicates otherwise. The terms "comprises", "comprising", "including", and "has" are inclusive and therefore specify the presence of stated features, steps, operations, elements, and / or components, but do not preclude the presence or addition of one or more other features, steps, operations, elements, components, and / or groups thereof. The method steps, processes, and operations described herein are not to be construed as necessarily requiring their performance in the particular order in which they are discussed or illustrated, unless specifically identified as an order of performance. Additional or alternative steps can be employed.

[0031] It should be noted that like reference numerals and letters refer to like items throughout the several views, and that once an item is defined in one view, it should not require further defining and explaining in the subsequent views.

[0032] Some embodiments of the present application will be described in detail with reference to the drawings, which are given by way of illustration and are not limitative of the present application. The embodiments and features described below can be combined with each other, without conflict, if not incompatible.

[0033] The positive electrode sheet of the lithium ion battery provided by the embodiments of the present disclosure comprises: a current collector and first and second positive electrode coatings respectively arranged on both sides of the current collector; the surfaces of the first and second positive electrode coatings are provided with a plurality of conical hole grooves; and the first and second positive electrode coatings respectively comprise quaternary system active material and transition metal doped lithium iron manganese phosphate, and the mass ratio of the quaternary system active material and the transition metal doped lithium iron manganese phosphate is 7:3-9:1; the chemical general formula of the quaternary system active material is LiNi x Co y Mn z Al 1-x-y-z O2, wherein 0.87≤x≤0.94, 0.03≤y≤0.06, 0.01≤z≤0.05 and x+y≤0.99; and the chemical formula of the transition metal doped lithium iron manganese phosphate is LiMn a Fe b M c PO4, wherein 0.4≤a≤0.6, 0.4≤b≤0.6 and c=1-a-b, and M comprises one or a combination of Mg, Ti, Zr, Nb, Ni, Co, F, B, etc.

[0034] In some embodiments, specifically, the quaternary system active material comprises quaternary system active material large particles and quaternary system active material small particles; wherein the D50 particle size of the quaternary system active material large particles is 9-13 μm, and the particle size distribution satisfies 0.2≤(D90-D10) / D50≤0.6; and the D50 of the quaternary system active material small particles is 2.5-5 μm, and the particle size distribution satisfies 1.1≤(D90-D10) / D50≤1.6.

[0035] In some embodiments, specifically, the positive electrode coating further comprises a conductive agent; the conductive agent is a carbon nanotube and graphene composite, and the mass ratio of the conductive agent to the total mass of the positive electrode coating is 2-5%.

[0036] In some embodiments, specifically, the lithium iron manganese phosphate is of a core-shell structure, the inner core is FePO4, and the volume ratio is 85%-92%, and the shell is LiMn aPO4, accounting for 8% to 15% by volume; wherein, the shell thickness is 50 to 100 nm.

[0037] In some embodiments, specifically, the tap density of the lithium manganese iron phosphate is ≥2.3 g / cm 3 , with a specific surface area of ​​5 to 10 m 2 / g.

[0038] In some embodiments, specifically, the positive electrode coating further includes a doped-coated composite compound, wherein the dopant includes any one or a combination of Al, Co, Ta, Ti, Nb, Zr, B, W, Mg, Te, Ca, Fe, Mo, Na, K, La, Ga, F, Cl, S, B and N.

[0039] In some embodiments, specifically, the current collector is aluminum foil coated with a carbon layer, the carbon layer has a thickness of 0.5 to 2 μm and a porosity of 15 to 25%; and the peel strength between the positive electrode coating and the current collector is ≥10 N / m.

[0040] See also Figure 2 and Figure 3 ,like Figure 2 and Figure 3 As shown, Figure 2 The second punching area 9 is located on the other side of the positive electrode sheet for a perspective effect; specifically, the width of the positive electrode sheet is L1, satisfying 50mm≤L1≤120mm, and the distances between the conical hole groove and the two sides of the positive electrode sheet in the width direction are D1 and D2 respectively; the thickness of the first positive electrode coating is h1, satisfying 40μm≤h1≤200μm, and the depth of the conical hole groove is h3; the thickness of the second positive electrode coating is h2, satisfying 40μm≤h2≤200μm, and the depth of the conical hole groove is h4; and the positive electrode sheet also satisfies: 0.2L1≤D1≤0.23L1; 0.2L1≤D2≤0.23L1; 0.78≤h3 / h1≤0.85; 0.78≤h4 / h2≤0.85.

[0041] See also Figure 1 ,like Figure 1 As shown, an embodiment of the present disclosure further provides a lithium-ion battery, comprising the lithium-ion battery positive electrode plate as described above.

[0042] The embodiment of the present disclosure further provides an electrical device, comprising the lithium-ion battery as described above.

[0043] Example 1:

[0044] Preparation of positive electrode sheet: the active material of the quaternary system is LiNi 0.90 Co 0.04 Mn 0.04 Al 0.02O2, mass ratio 80%, transition metal doped lithium iron manganese phosphate LiMn 0.6 Fe 0.4 PO4, mass ratio 20%, quaternary system active material and transition metal doped lithium iron manganese phosphate accounts for 96% of the total amount of positive electrode formula, and 2% of polyvinylidene fluoride PVDF binder and 2% of Super-P (conductive carbon black) conductive agent are added; the above-mentioned substances are added to the solvent NMP to obtain a positive electrode slurry with a solid content of 68%, which is coated on both sides of the aluminum foil to obtain a positive electrode sheet.

[0045] The negative electrode sheet preparation method comprises a negative electrode current collector copper foil and a negative electrode active material layer coated on both sides of the current collector, wherein the negative electrode coating comprises 96% artificial graphite and silicon carbon, 1.0% conductive agent, 1.0% thickening agent and 2% binder according to mass percentage, the above-mentioned materials are added to the solvent deionized water to obtain a negative electrode slurry with a solid content of 40%, which is coated on both sides of the copper foil to obtain a negative electrode sheet.

[0046] The electrolyte preparation method comprises dissolving lithium salt LiPF6 in an organic solvent prepared by mixing ethylene carbonate (EC), diethyl carbonate (DEC) and methyl ethyl carbonate in a volume ratio of 1:1:1, wherein the additive content is 0.2%-5%, and finally configuring the electrolyte with a concentration of 1 mol / L.

[0047] The separator preparation method comprises a high porosity separator, a base film PE with a thickness of 9 μm, ceramic coating on both sides with a thickness of 1 μm, and PVDF coating with a thickness of 1 μm, and the air permeability of the separator is ≤100 s / 100 mL.

[0048] The assembly method comprises punching the positive electrode sheet in the coating area by laser, wherein D1=0.2L1, D2=0.21L1, h3 / h1=0.8, h4 / h2=0.8, then slitting and die cutting the positive electrode sheet and the negative electrode sheet, and winding the separator at the same time, the battery roll core body is loaded into the battery shell, and the experimental battery is obtained after completing the liquid injection, sealing and formation processes.

[0049] Examples 2-7 and Comparative Examples 1-4 are obtained according to the step change parameters of Example 1, and the change parameters and test results are shown in Table 1.

[0050] Table 1

[0051]

[0052] Test 1: capacity retention rate test after 500 cycles, 45℃, 1C / 1C

[0053] Take a fresh battery, place it in a 45℃ constant temperature oven for more than 4h, and test according to the following steps:

[0054] (1) Discharge the battery at a constant current of 0.1C to a cutoff of 2.5V and let it stand for 5 minutes;

[0055] (2) Charge the battery at a constant current of 0.2C to a cutoff of 4.2V, and at a constant voltage of 0.05C to a cutoff, and let it rest for 5 minutes;

[0056] (3) Discharge the battery at a constant current of 0.2C to a cutoff of 2.5V, let it stand for 5 minutes, and read the capacity value C0 at this time;

[0057] (4) Charge the battery at a constant current of 1.0C to 4.2V, and charge it at a constant voltage of 0.05C, and let it rest for 5 minutes.

[0058] (5) Discharge the battery at a constant current of 1.0C to a cutoff of 2.5V and let it stand for 5 minutes;

[0059] (6) Repeat steps (4) and (5) 500 times;

[0060] (7) The discharge capacity at the 500th cycle and the first cycle, i.e., the capacity retention rate.

[0061] Test 2: Hot box test

[0062] Take a fresh battery, place it in a 25℃ constant temperature box for more than 4 hours, and test it according to the following steps:

[0063] (1) Discharge the battery at a constant current of 0.1C to a cutoff of 2.5V and let it stand for 5 minutes;

[0064] (2) Charge the battery at a constant current of 0.2C to a cutoff of 4.2V, and at a constant voltage of 0.05C to a cutoff, and let it rest for 5 minutes;

[0065] (3) Place the battery in a constant temperature box, set the heating rate to 5K / min, heat it to 130°C, and keep it for 0.5h, then stop heating and allow it to cool down to below 30°C by self-heating;

[0066] (4) If the battery does not catch fire or emit smoke, it is considered passed; otherwise, it is failed. At least 5 batteries are tested and the pass rate is recorded.

[0067] Test 3: 5C rate capacity retention test

[0068] Take a cylindrical battery of this application, place the battery in a 25°C constant temperature box for more than 4 hours, with the voltage window of 2.5-4.2V, and test it according to the following steps:

[0069] (1) Discharge the battery at a constant current of 0.1C to a cutoff of 2.5V and let it stand for 10 minutes;

[0070] (2) Charge the battery at a constant current of 0.1C to a cutoff of 4.2V, and at a constant voltage of 0.01C to a cutoff, and let it rest for 10 minutes.

[0071] (3) Discharge the battery at a constant current of 0.1C to a cutoff of 2.5V, let it stand for 10 minutes, and read the capacity value C0 at this time;

[0072] (4) Charge the battery at a constant current of 0.1C to 4.2V, and charge it at a constant voltage of 0.01C, and let it rest for 10 minutes.

[0073] (5) Discharge the battery at a constant current of 0.5C to a cutoff of 2.5V and let it stand for 10 minutes;

[0074] (6) Charge the battery at a constant current of 0.1C to 4.2V, and charge it at a constant voltage of 0.01C, and let it rest for 10 minutes.

[0075] (7) Discharge the battery at a constant current of 1C to a cutoff of 2.5V and let it stand for 10 minutes;

[0076] (8) Charge the battery at a constant current of 0.1C to 4.2V, and charge it at a constant voltage of 0.01C, and let it rest for 10 minutes.

[0077] (9) Discharge the battery at a constant current of 2C to a cutoff of 2.5V and let it stand for 10 minutes;

[0078] (10) Charge the battery at a constant current of 0.1C to 4.2V, and charge it at a constant voltage of 0.01C, and let it rest for 10 minutes.

[0079] (11) Discharge the battery at a constant current of 3C to a cutoff of 2.5V and let it stand for 10 minutes;

[0080] (12) Charge the battery at a constant current of 0.1C to 4.2V, and charge it at a constant voltage of 0.01C, and let it rest for 10 minutes.

[0081] (13) Discharge the battery at a constant current of 4C to a cutoff of 2.5V and let it stand for 10 minutes;

[0082] (14) Charge the battery at a constant current of 0.1C to 4.2V, and charge it at a constant voltage of 0.01C, and let it rest for 10 minutes.

[0083] (15) Discharge the battery at a constant current of 5C to a cutoff of 2.5V and let it stand for 10 minutes;

[0084] (16) The rate performance of a single battery, i.e., the 5C rate capacity retention rate, is obtained by calculating the ratio of the 5C rate discharge capacity to the first discharge capacity.

[0085] Specifically, the Ni content in the quaternary system active material in Comparative Example 1 exceeds the range of 0.87≤x≤0.94, and the Mn content in the transition metal-doped lithium iron manganese phosphate is lower than the range of 0.4≤a≤0.6. At this ratio, the lithium iron manganese phosphate cannot be combined with the high-nickel material active material, and therefore the thermal stability is insufficient to pass the hot box test.

[0086] Specifically, in Comparative Example 2, the mass ratio of the quaternary system active material to the transition metal-doped lithium iron manganese phosphate is 5:5, which is also impossible to be combined. Therefore, the thermal stability is insufficient and it cannot pass the hot box test. In addition, the excessively high lithium iron manganese phosphate has no high nickel material to provide high conductivity, and the cycle retention performance also declines significantly.

[0087] Specifically, in Comparative Example 3, lithium manganese iron phosphate was not added as an additive, so the capacity retention rate and hot box test of the lithium-ion battery failed.

[0088] Specifically, the Ni content in Comparative Example 4 is lower than the range of 0.87≤x≤0.94, and the Mn content in the transition metal-doped lithium iron manganese phosphate exceeds the range of 0.4≤a≤0.6. At this ratio, the lithium iron manganese phosphate cannot be combined with the high-nickel material active substance, so the thermal stability is insufficient to pass the hot box test, and the cycle retention performance also declines significantly.

[0089] In summary, the lithium-ion battery positive electrode plate, lithium-ion battery, and electrical device utilize high-nickel material active substances to improve the overall energy density of the battery. Its high electronic conductivity can improve the kinetic performance of the lithium iron manganese phosphate material, and the mixed use of the two can not only reduce the dependence on cobalt, but also utilize the olivine structure of the lithium iron manganese phosphate material to provide thermal stability of the high-nickel material, and can also slow down the capacity decay of the high-nickel material in long cycles; in addition, the perforated design of the positive electrode plate can improve the wettability of the electrolyte to the plate, thereby enhancing the lithium ion intercalation and deintercalation ability, improving the kinetic performance, and improving the battery's long thermal cycle charge and discharge performance and stability.

[0090] With the above-described preferred embodiments of the present invention as a guide, and with reference to the above description, relevant personnel are fully capable of making various changes and modifications without departing from the technical scope of this invention. The technical scope of this invention is not limited to the contents of the specification and must be determined according to the scope of the claims.

Claims

1. A lithium-ion battery positive electrode plate, characterized in that: include: A current collector and a first positive electrode coating and a second positive electrode coating respectively disposed on both sides of the current collector; The surfaces of the first positive electrode coating and the second positive electrode coating are punched with a plurality of conical holes; Furthermore, the first positive electrode coating and the second positive electrode coating respectively comprise a quaternary system active material and transition metal-doped lithium iron manganese phosphate, wherein the mass ratio of the quaternary system active material to the transition metal-doped lithium iron manganese phosphate is 7:3 to 9:1; The chemical formula of the quaternary system active material is LiNi x Co y Mn z Al 1-x-y-z O2, where 0.87≤x≤0.94, 0.03≤y≤0.06, 0.01≤z≤0.05 and x+y≤0.99; The chemical formula of the transition metal doped lithium iron manganese phosphate is LiMn a Fe b M c PO4, wherein 0.4≤a≤0.6, 0.4≤b≤0.6, and c=1-ab, and M includes one or a combination of Mg, Ti, Zr, Nb, Ni, Co, F, B, etc.

2. The positive electrode plate of a lithium-ion battery according to claim 1, wherein: The quaternary system active substance includes large quaternary system active substance particles and small quaternary system active substance particles; The D50 particle size of the large particles of the quaternary system active substance is 9 to 13 μm, and the particle size distribution satisfies 0.2≤(D90-D10) / D50≤0.6; The D50 of the small particles of the quaternary system active substance is 2.5 to 5 μm, and the particle size distribution satisfies 1.1≤(D90-D10) / D50≤1.

6.

3. The positive electrode plate of a lithium-ion battery according to claim 2, wherein: The positive electrode coating further includes a conductive agent; The conductive agent is a composite of carbon nanotubes and graphene, and the mass of the conductive agent accounts for 2-5% of the total mass of the positive electrode coating.

4. The positive electrode plate of a lithium-ion battery according to claim 1, wherein: The lithium iron manganese phosphate has a core-shell structure, wherein the core is FePO4, which accounts for 85% to 92% of the volume, and the outer shell is LiMn a PO4, accounting for 8% to 15% by volume; The shell thickness is 50 to 100 nm.

5. The positive electrode plate of a lithium-ion battery according to claim 4, wherein: The tap density of the lithium manganese iron phosphate is ≥2.3g / cm 3 , with a specific surface area of ​​5 to 10 m 2 / g.

6. The positive electrode plate of a lithium-ion battery according to claim 1, wherein: The positive electrode coating also includes a doped and coated composite compound, wherein the dopant includes any one or a combination of Al, Co, Ta, Ti, Nb, Zr, B, W, Mg, Te, Ca, Fe, Mo, Na, K, La, Ga, F, Cl, S, B and N.

7. The positive electrode plate of a lithium-ion battery according to claim 1, wherein: The current collector is an aluminum foil coated with a carbon layer, the carbon layer has a thickness of 0.5 to 2 μm and a porosity of 15 to 25%; The peeling strength between the positive electrode coating and the current collector is ≥10N / m.

8. The lithium-ion battery positive electrode sheet according to claim 1, wherein: The width of the positive electrode sheet is L1, which satisfies 50 mm ≤ L1 ≤ 120 mm, and the distances between the conical hole and the two sides of the positive electrode sheet in the width direction are D1 and D2 respectively; The thickness of the first positive electrode coating is h1, which satisfies 40 μm≤h1≤200 μm, and the depth of the conical hole groove is h3; The thickness of the second positive electrode coating is h2, which satisfies 40 μm ≤ h2 ≤ 200 μm, and the depth of the conical hole groove is h4; Furthermore, the positive electrode plate also satisfies: 0.2L1≤D1≤0.23L1; 0.2L1≤D2≤0.23L1; 0.78≤h3 / h1≤0.85; 0.78≤h4 / h2≤0.

85.

9. A lithium-ion battery, characterized in that: The invention comprises a positive electrode sheet of a lithium-ion battery as claimed in any one of claims 1 to 8.

10. An electrical device, characterized in that: Comprising the lithium-ion battery as claimed in claim 9.